Multifrequency EPR study of HWCVD μc‐SiC:H for photovoltaic applications. Issue 7 (4th March 2016) - Astakhov, Oleksandr; Xiao, Lihong; Finger, Friedhelm; Chen, Tao; Fehr, Matthias; George, Benjamin; Schnegg, Alexander; Lips, Klaus; Teutloff, Christian
Abstract : Microcrystalline silicon carbide alloys (μc‐SiC:H) have attracted attention as a potential window layer for thin film silicon solar cells and silicon heterojunction solar cells. Thanks to the combination of high transparency and conductivity. At present, identification of electronically active impurities and defects is highly relevant for application of μc‐SiC:H. Electron paramagnetic resonance has been successfully applied to investigate defects and impurities in crystalline SiC. Continuous wave X‐band EPR measurements performed earlier on a number of μc‐SiC:H samples show intensive and complex spectra with multiple overlapped components. In order to resolve components of the μc‐SiC:H spectra, we performed a series of pulsed EPR measurements in S‐, X‐, and Q‐band completed with a Q‐band ENDOR experiment. The experiment was successful to resolve hidden complexity of the EPR spectra of μc‐SiC:H and determine the nucleus responsible for the hyperfine pattern observed in previous studies.